(untitled) (Sociología y tecnociencia, 2020)
This article presents the results of a qualitative research on the imprint of neoliberal rationality in the organization of scientific production, in its objectives and its field of action, as well as in the redefinition of the figure of the young researcher (PhD students and postdoctoral students). I point out that all the transformations in these fields are the result of scientific policies, whose most obvious products are the excellent research centres and the figure of entrepreneur-researcher. I argue that the entrepreneurial identity of young researchers and the organizational flexibility of excellent research centres are mutually co-construct and interdependent. Likewise, I conclude that neoliberalized science excludes all those who don’t share the same productive values, and how the system prevents possible disobediences